Okun’s Law: Analisis Tingkat Pengangguran Terbuka Kabupaten Banjar Ditinjau dari Perspektif Laju Pertumbuhan Ekonomi - Rafli, Muhammad Raihan; Nurhafiyanisa, Nurhafiyanisa; Syafa, Mona Khairida; Aisyah, Lisda (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
Unemployment is one of the main problems that is very influential and is also affected by several factors that are interrelated with each other and have a close relationship with the unemployment rate; this is because the working population contributes to the production of goods and services. Based on data obtained from the Central Bureau of Statistics, it was found that in the 2018-2021 period, there was a positive relationship between economic growth and open unemployment, and there were doubts due to the rejection of previous research results, so it is possible to analyze the level of open unemployment in Banjar Regency in terms of the rate of economic growth in 2017-2022 using the Okun's Law theory approach. This research uses a quantitative method with time series analysis using simple linear regression analysis to obtain Okun's coefficient. The results found that economic growth has no significant negative effect on the unemployment rate. In addition, the insignificant value of Okun's coefficient indicates a negatively unresponsive unemployment rate in Kabupaten Banjar, and there is an insignificant negative relationship between economic growth and the open unemployment rate. Therefore, Okun's law theory is proven not to apply in the economy of Kabupaten Banjar.